Literature, education, and romanticism reading as social practice, 1780 - 1832 - Richardson, Alan (Cambridge Univ. Press, 1994)
Romantic texts - by Wordsworth, Shelley, Blake, and Yearsley among others - are reinterpreted in the light of the complex historical and social issues which inform them, and which they in turn critically address
Keywords: Geschichte 1700-1800; Geschichte 1800-1900; Geschichte 1780-1832; Educação (história) - Grã-bretanha; Engels; Leitura (história; aspectos sociais) - Grã-bretanha; Letterkunde; Lezen; Literatura (sociedade; história) - Grã-bretanha; Literatura inglesa (história e crítica) - Seculo 18; seculo 19; Onderwijs; Romantismo - Grã-bretanha; Englisch; Erziehung; Geschichte; Gesellschaft; Literatur; Unterricht; Books and reading -- Social aspects -- Great Britain -- History; Education -- Great Britain -- History; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 18th century; Literature and society -- Great Britain -- History -- 19th century; Romanticism -- Great Britain; Literarisches Leben; Kinderliteratur; Romantik; Bildung; Leserin; Leser; Bildungswesen; Schulbildung; Großbritannien